If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 + 3x = -91 + -10x Solving 13 + 3x = -91 + -10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10x' to each side of the equation. 13 + 3x + 10x = -91 + -10x + 10x Combine like terms: 3x + 10x = 13x 13 + 13x = -91 + -10x + 10x Combine like terms: -10x + 10x = 0 13 + 13x = -91 + 0 13 + 13x = -91 Add '-13' to each side of the equation. 13 + -13 + 13x = -91 + -13 Combine like terms: 13 + -13 = 0 0 + 13x = -91 + -13 13x = -91 + -13 Combine like terms: -91 + -13 = -104 13x = -104 Divide each side by '13'. x = -8 Simplifying x = -8
| 2x+15=4x+11 | | 34m-5-1/2m=1 | | 24-4x=9-7x | | X-(7x-8)= | | 8x-y=32 | | 5/6=1/x | | a+3b-4c=0 | | y=zx-2x+5 | | 18-x=x-2 | | 6y+2x=16 | | 5ex=15.76 | | (a+2b)(a^2-2ab+4b^2)= | | (m+1)(m^2-m+1)= | | (2a-b)(2a-b)= | | x+5*7=133 | | cos(x)=0.333333 | | sin(x)=0.33 | | -4x^2y^2= | | 12(3n-5)= | | 8x15sequre15/8x5sequre | | X^2-(p-2)x+2p+1=0 | | X+(5y)=65 | | 3x+10=28-3x | | 2(2x+8)=2(3x+8) | | X+.2x=2400 | | 2x+(4-4)=8-4 | | 4e-7= | | 5.3x-1.4=2.2-5.3x | | 6[-5x-6+2(2x+1)]=-3x+4 | | 9x-16y= | | 7x-6=24-x | | -s^3+7s^2-15s-24=0 |